Role of data and graph interpretation in inquiry based physics laboratory - Ari, Üzeyir; Peşman, Haki (Sakarya University, 2016)
In this study, inquiry teaching was used to overcome prospective elementary science teachers’ misconceptions in Newtonian mechanics. Because students have difficulty in drawing a conclusion by themselves in inquiry teaching, some additional teaching techniques were used in one group so that students could draw the desired conclusions (scaffolded inquiry teaching). In the end of the treatments, students took a three-tier diagnostic test on mechanics to assess their misconceptions. Accordingly, there were no significant difference between mean misconception scores in mechanics (t = - .311; p = .76). However, prior to do treatments, a Science Process Skills Test had been administered and whether students with different levels of process skills are influenced in the same way by the treatments was also investigated using the Johnson-Neyman technique. Accordingly, any interactions could not be observed for the dimensions apart from the data and graph interpretation. In conclusion, scaffolded inquiry teaching seems to be more effective for students with high level of data and graph interpretation. © The Turkish Online Journal of Educational Technology.